Antibody response to Phlebotomus perniciosus saliva in cats naturally exposed to phlebotomine sand flies is positively associated with Leishmania infection - Pereira, André (2019)
BACKGROUND: Zoonotic leishmaniosis, caused by the protozoan Leishmania infantum, is a public and animal health problem in Asia, Central and South America, the Middle East and the Mediterranean Basin. Several phlebotomine sand fly species from the subgenus Larroussius are vectors of L. infantum. Data from dogs living in endemic areas of leishmaniosis advocate the use of antibody response to phlebotomine sand fly saliva as an epidemiological biomarker for monitoring vector exposure. The aim of this study was to analyse the exposure of cats to phlebotomine sand flies using detection of IgG antibodies to Phlebotomus perniciosus saliva. The association between phlebotomine sand fly exposure and the presence of Leishmania infection was also investigated. RESULTS: IgG antibodies to P. perniciosus saliva were detected in 167 (47.7%) out of 350 cats; higher antibody levels were present in sera collected during the period of phlebotomine sand fly seasonal activity (OR = 19.44, 95% CI: 9.84-38.41). Cats of 12-35 months had higher antibody levels than younger ones (OR = 3.56, 95% CI: 1.39-9.16); this difference was also significant with older cats (for 36-95 months-old, OR = 9.43, 95% CI: 3.62-24.48; for older than 95 months, OR = 9.68, 95% CI: 3.92-23.91). Leishmania spp. DNA was detected in the blood of 24 (6.9%) cats, while antibodies to L. infantum were detected in three (0.9%). Only one cat was positive to Leishmania by both techniques. Cats presenting IgG antibodies to P. perniciosus had a significantly higher risk of being positive for Leishmania infection. CONCLUSIONS: To our knowledge, this is the first study demonstrating anti-sand fly saliva antibodies in cats. The evaluation of the contact of this animal species with the vector is important to the development of prophylactic measures directed to cats, with the aim of reducing the prevalence of infection in an endemic area. Therefore, studies evaluating whether the use of imidacloprid/flumethrin collars reduces the frequency of P. perniciosus bites in cats are needed. It is also important to evaluate if there is a correlation between the number of phlebotomine sand fly bites and IgG antibody levels.